The Sometimes Antisocial Nature of Nanofibrillated Cellulose and Some Other Papermaking Fiber Surfaces - Martin A. Hubbe (BioResources, 2025)
The word “antisocial” appears to well describe some aspects that have been observed when nanofibrillated cellulose (NFC) has been added to papermaking fiber suspensions, in combination with some chemical additives that are commonly used in that process. The analogies of folded hands or a clenched fist can be used to convey a hypothesis of an inability of certain cellulosic fibrils to become engaged in a microscopic three-dimensional structure, which appears to be essential for the development of paper strength. Though this editorial points to some important drawbacks of NFC as an additive for conventional papermaking, it also sheds more light on the wisdom of conventional pulp refining technology. One can envision refining partly as a way to activate cellulosic nanofibrils at the fiber surfaces such that they are ready to intertwine with each other efficiently at a nano scale during the formation of the sheet. In this way they can achieve a favorable combination of dewatering rate, efficient of retention of the fibrillated matter, and notable increases in strength properties.